EFFECT OF PLANT POPULATION DENSITIES ON YIELD OF MAIZE - M. R. Abuzar; G. U. Sadozai; M. S. Baloch; A. A. Baloch; I. H. Shah; T. Javaid; N. Hussain (Journal of Animal and Plant Sciences, 2011)
A field experiment to determine the effect of plant population densities on maize was conducted at the Agricultural Research Institute, Dera Ismail Khan, in mid July 2009. The effect of six plant population densities i.e. T1 (40000 plants ha–1), T2 (60000 plant ha–1), T3 (80000 plants ha–1), T4 (100000 plants ha–1), T5 (120,000 plants ha–1) and T6 (140,000 plants ha–1) was investigated using maize variety Azam. Results showed that plant population of 40000 ha–1 produced maximum number of grains per row (32.33) and grains per ear (447.3). However, 60000 plants ha–1 produced the maximum number of ears per plant (1.33), number of grain rows per ear (15.44), biomass yield (16890 kg ha–1) and grain yield (2604 kg ha–1). Therefore, planting density of 60000 plants ha–1 (keeping plant to plant distance of 22.70cm) is recommended for obtaining higher yield of maize.
Keywords: Biomass; grain yield; maize; population density